Evaluation De L#x2019;activit#xE9; Anthelminthique Des Extraits Aqueux De Striga Hermonthica (Del.) Benth Et Ceratotheca S#xE9;samo#xEF;des Endl Sur Deux Stades Biologiques De Haemonchus Contortus (Global Journal of Medical Research, 2021)
Medicinal plants with anthelmintic properties are an alternative to the chemical fight against small ruminant#x2019;s gastrointestinal nematodes. In order to broaden the spectrum of medicinal plants with anthelmintic properties, ovicidal activity and L3 larvae exsheathment of C. sesamo#xEF;des Endl and S. hermonthica (Deli) Benth, aqueous extracts has been done on H contortus egg and L3 larvae. Three concentrations, 3.12 mg / ml, 6.25 mg / ml, 12.5 mg / ml of each plant extract were used to assess the inhibition of fresh egg hatching and larval paralysis as well as the 'inhibition of L3 larvae exsheathment. A negative control (PBS1x) and a positive control (levamisole, 2.5 mg / ml) were constituted for the fresh egg hatching inhibition assessment while only the negative control (PBS1x) was constituted to evaluate the inhibition of L3 Larvae exsheathment.1 ml of each concentration was contacted with 1 ml of the egg solution and then incubated for 48 hours at 27 #xB0; C in petri dishes (60X15 Cm) for hatching test inhibition.1 ml of each extract concentration was contacted with 1 ml of the embryonated egg solution after 24 hours of incubation at 27 #xB0; C for the larval paralysis test.
Keywords: ceratoth#xE9; ca sesamoides endl; striga hermonthica (Deli) benth; H contortus; egg hatching inhibition; L3 larval exsheathment inhibition